Molecular dynamics approach to understand the denaturing effect of a millimolar concentration of dodine on a λ-repressor and counteraction by trehalose. Issue 20 (10th May 2017) - Borgohain, Gargi; Mandal, Bikramaditya; Paul, Sandip
Abstract : Here, we use a molecular dynamics approach to calculate the spatial distribution function of the ternary water–dodine–trehalose (1.0 M) system. Abstract : Commonly used denaturants for protein denaturation are conventionally required in high concentrations in order to produce their effects. In this study, a molecular dynamics simulation of a mutated version of the N-terminal domain of a λ-repressor is carried out in the presence of a 10 millimolar (mM) concentration of dodine. Such a small concentration is found to be effective for denaturation of the protein. Both electrostatic and van der Waals interactions (between protein and dodine) play a role in the denaturation process and we observe more denaturation at the terminal helices. Three different molar concentrations of trehalose are used in order to check the counteraction against the action of dodine. This study shows that 0.5 and 1.0 M trehalose are sufficient to counteract the action of dodine. The study also sheds light on the fact that some protein sites are more responsive to unfolding, which is evident from the helical fractions of the terminal helices for different systems. The counteraction of trehalose on dodine-induced protein denaturation is found to be due to the replacement of some of the dodine molecules by trehalose molecules in the solvation shell of the protein. Preferential solvation of dodine molecules by trehalose molecules through hydrogen bonding interactions also plays a vital role in stabilizing the native conformation of the protein in a high trehalose concentration. Replacement of protein–dodine and protein–water hydrogen bonds by protein–trehalose hydrogen bonds is also observed.